ANALISIS KESUKSESAN BAHAN ALAM SEBAGAI PENGHASIL PRODUK SENYAWA OBAT ESENSIAL - Wulandari Dewi, Ni Putu Ayu (Usadha, 2022)
The use of natural ingredients is a quandary and a dynamic in the world of drugs in the pharmaceutical industry. The number of paradigms that are compared with research as proof that natural ingredients can produce products as essential medicinal compounds is a study that continues to be proven and developed through biotechnology and chemical processes. In the article in this journal, the type of research method used is qualitative with descriptive analysis using the literature study method. The descriptive qualitative method is carried out to analyze and describe the results of the research through observation in the study of literature with relevant sources related to the discussion of the subjects studied in the research in this journal. The results of the discussion of the research are that natural ingredients are very essential to become medicinal compounds seen from the production process and utilization. Keywords : Medicine, Natural Ingredients, Essential